The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 1st Economics and Business International Conference 2017 (EBIC 2017) 2018
DOI: 10.2991/ebic-17.2018.62
|View full text |Cite
|
Sign up to set email alerts
|

Influence Of Servicescape, Customer Satisfaction, WOM, and Social Media to Consumer Loyalty (study case bali beach)

Abstract: Indonesia have blessed with many beautiful natural scenery. This beautiful gift of nature must be kept to the best possible so that it can be enjoyed by many peopleand become a source of local income. The purpose of this study was to determine the influence of Servicescape, Customer satisfaction, Word of Mouth, and Social Media, to visiting interest local and foreign tourist to Bali Beach Lestari,Serdang Bedagai,North of Sumatra, Indonesia. The type of research is a causal associative research with data collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 38 publications
0
6
0
4
Order By: Relevance
“…Kepuasan konsumen adalah perasaan yang timbul baik senang ataupun kecewa dari pelanggan setelah melakukan perbandingan antara, kinerja (hasil) yang didapatkan dengan ekspektasinya. (Situmorang, 2018) Beberapa keuntungan yang akan didapatkan juga pelanggan merasa puas diantaranya: hubungan harmonis antara pelanggan dan perusahaan dapat terjalin dengan baik dan baik, menjadi dasar yang cukup baik dan kuat bagi pelanggan untuk melakukan pembelian kembali, mendorong terciptanya pelanggan yang loyal, dan timbulnya kesediaan pelanggan untuk melakukan pembayaran dengan harga yang dianggapnya wajar atas jasa yang sudah diterimanya. (Lin et al, 2017)…”
Section: Teori Kepuasan Pelanggan (Customer Satisfaction)unclassified
“…Kepuasan konsumen adalah perasaan yang timbul baik senang ataupun kecewa dari pelanggan setelah melakukan perbandingan antara, kinerja (hasil) yang didapatkan dengan ekspektasinya. (Situmorang, 2018) Beberapa keuntungan yang akan didapatkan juga pelanggan merasa puas diantaranya: hubungan harmonis antara pelanggan dan perusahaan dapat terjalin dengan baik dan baik, menjadi dasar yang cukup baik dan kuat bagi pelanggan untuk melakukan pembelian kembali, mendorong terciptanya pelanggan yang loyal, dan timbulnya kesediaan pelanggan untuk melakukan pembayaran dengan harga yang dianggapnya wajar atas jasa yang sudah diterimanya. (Lin et al, 2017)…”
Section: Teori Kepuasan Pelanggan (Customer Satisfaction)unclassified
“…Penerapan servicescape dinilai pilihan yang tepat digunakan untuk mendapatkan perhatian calon pelanggan. Servicescape juga dipandang sebagai lingkungan layanan yang diciptakan untuk pelanggan dan pelanggan dan penyedia layanan dapat berinteraksi (Situmorang, 2018). Tujuan dari penerapan servicescape adalah untuk memuaskan pelanggan (Ariani, 2009).…”
Section: Latar Belakangunclassified
“…Hasil temuan lain mengungkapkan hal yang berbeda (Situmorang, 2018) mengungkapkan bahawa implementasi serviscape memberikan pengaruh positif tetapi tidak signifikan terhadap revisit intention. Abuthahir & Krishnapillai, (2018) mengungkapkan hal yang sama bahwa Ambient Conditions tidak berpengaruh terhadap revisit intention sedangkan 2 dimensi lain yang membentuk servicescape yaitu Spatial and Functionality dan Signs, Symbols, and Artifacts berpengaruh positif tetapi tidak signifikan.…”
Section: Latar Belakangunclassified
See 1 more Smart Citation
“…On the other hand, dissatisfaction can cause impacts in the reputation of the hotel and to its general aspects (De Guzman et al, 2020) To further familiarize guests to the actual establishments, technology had created the most effective and efficient way to assess the target area, through an online review from reliable sites found on the internet. These sites such as Agoda, TripAdvisor and Expedia are some of the examples of sites that have an honest context of reviews that can aid the questions of each planning guest (Situmorang, 2018). Reliable reviews from the sites are simple tools that could affect the beach hotel's reputation that could branched into two aspects, might be negative review that could affect the overall profit, status of the beach hotel and reduce the probability of return of previous guests and on the other side of the spectrum, positive reviews that could further boost the management's service through a simple recognition (Situmorang, 2018).…”
Section: Introductionmentioning
confidence: 99%